The inadmissibility of the appeal (SCIÉNDO INGENIUM, 2022)
The current validity of article 423 section 3 of the NCPP of 2004 is questioned; and, the importance of its reformulation. Reformulating the aforementioned normative precept is due to the importance of the precautionary materialization that the State possesses with respect to the judicial control of the sentence. We accept the validity of a restricted appeal system; however, we consider that this position is only rigorously applicable in specific cases in which the validity, certainty or credibility of the personal evidence must be determined or also in the face of questions related to the foundability of the facts invoked in the appealed judgment. At the national level, the strict application of the aforementioned legal device imports the transcendental loss of judicial control over the A Quo, under unfounded criteria of respect for the principle of immediacy, orality and contradiction, there is a risk of consenting to illegal judicial pronouncements. The need for the appellant to be physically present cannot constitute a limitation to the duty of control exercised by the Superior Court of Appeal over the errors in iudicando; therefore, its current validity constitutes a way of destabilizing the Criminal Justice System.
Keywords: The Inadmissibility of the Appeal; Appeal; Inadmissible